MODELING GRAVITATIONAL TRAJECTORIES AROUND BIG MACROSCOPIC OBJECTS BY MEANS OF NESTED FUNCTIONS IN THE FORM OF PARAMETRIC EQUATIONS - José D. Ávila (Momento, 2016)
This paper will expound how to obtain a parametric equation that make possible to model orbital trajectories of objects around large macroscopic bodies, in special black holes, without the use of tensor calculus. The mathematical model allows the characterization of trajectories of pairs of black holes using parameters whose values depend mainly on whole numbers, in a way very similar to how some quantum numbers determine quantum states of the hydrogen atom, enabling a simple taxonomic system for them.